Subsurface dispersion path and travel time of radiocesium from Fukushima by Mode Water - Lee, Seung-Tae; Jung, Jihun; Kim, Guebuem; Tak, Yong-Jin; Cho, Yang-Ki (Frontiers in Marine Science, 2023)
The Fukushima Daiichi Nuclear Power Plant (FDNPP) accident on March 11, 2011 resulted in the release of immense amounts of radioactive materials into the ocean. However, the dispersion of radioactive materials in the subsurface has not yet been clarified due to the spatiotemporal limitation of observations. Thus, herein, a tracer experiment was implemented using a three-dimensional numerical model to estimate the dispersion path of 137Cs released directly from the FDNPP and its travel time in the subsurface of the North Pacific Ocean from 2011 to 2020. The results show that the subsurface 137Cs spreads by two mode waters, namely, Sub-Tropical Mode Water (STMW) and Central Mode Water (CMW). Subsurface 137Cs primarily spreads clockwise in the sub-tropical region, while a portion driven by STMW is dispersed southward. The clockwise dispersion path of 137Cs released into the ocean by STMW is relatively shallower and inward than that by CMW. The 137Cs that was spread clockwise reached the east of Taiwan and the Philippines via STMW and CMW nine years after the accident, respectively. The model described in this study is applicable for estimating the water path and travel time of tritium water planned to be discharged from Fukushima.